2019
DOI: 10.9734/ejmp/2019/v30i330179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acute and Sub-acute Toxicity of the Aqueous Extract from the Fruit of Solanum indicum Linn. (Solanaceae) in Rats

Abstract: Aim: The fruit of Solanum indicum Linn have been reported traditionally to have anti-hypertensive and diuretic properties. This study was undertaken to evaluate the toxicological potential of S. indicum fruits aqueous extract through the acute and sub-acute toxicity tests in rats. Methodology: For acute toxicity evaluation, a single oral dose of 5000 mg/kg of the plant extract was administrated in 60 days old female albino Wistar rats. Then, the animals were observed for 14 days. Sub-acute toxicity studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Controversy also exists regarding the safety of S. indicum L. fruit (SILF). Several authors have reported that SILF is safe, and thus, may be consumed as a vegetable [ 9 , 113 , 114 , 117 , 118 , 119 ], while one author has reported that it is a poisonous berry [ 115 ]. Similar to SALF, SILF has been reported to contain steroidal saponins/glycosides (isoanguivine, protodioscin, solasonine, solamargine, and indiosides A–E), terpenoids, vitamin C, phenolics (gallic acid, catechin, chlorogenic acid, caffeic acid, epicatechin), flavonoids (rutin, quercetin, isoquercitrin), glycoalkaloids (solamargine, solasonine) and coumarins [ 120 , 121 , 122 ].…”
Section: Solanum Anguivi Lam Fruit’s Antidiabementioning
confidence: 99%
“…Controversy also exists regarding the safety of S. indicum L. fruit (SILF). Several authors have reported that SILF is safe, and thus, may be consumed as a vegetable [ 9 , 113 , 114 , 117 , 118 , 119 ], while one author has reported that it is a poisonous berry [ 115 ]. Similar to SALF, SILF has been reported to contain steroidal saponins/glycosides (isoanguivine, protodioscin, solasonine, solamargine, and indiosides A–E), terpenoids, vitamin C, phenolics (gallic acid, catechin, chlorogenic acid, caffeic acid, epicatechin), flavonoids (rutin, quercetin, isoquercitrin), glycoalkaloids (solamargine, solasonine) and coumarins [ 120 , 121 , 122 ].…”
Section: Solanum Anguivi Lam Fruit’s Antidiabementioning
confidence: 99%